Impact of HPV Subtypes on Prognosis and Treatment in Oropharyngeal Cancers - Zeeshan, Muhammad; Malik, Pervaiz Azam; Mateen, Laiba; Aziz, Saqib; Uppal, Athar Adnan; Aslam, Huma; Aimen Ikram, Muhammad (Journal of Neonatal Surgery, 2025)
Background: Human papillomavirus (HPV) has been established as one of the significant causal factors for oropharyngeal squamous cell carcinoma (OPSCC). Although prognosis is usually favorable with HPV positivity, it appears that subtype variations may impact outcomes. To assess the impact of different HPV subtypes on clinical outcomes, treatment response, and survival in patients diagnosed with oropharyngeal cancers. Methods: An observational study was carried out between March 2023 and August 2024 with a sample of 81 HPV-positive OPSCC patients. The patients were classified into three groups according to the HPV subtypes as HPV-16, HPV-18, and other high-risk variants. The study analyzed several variables such as demographics, clinical characteristics , treatment received, and outcomes after one year. Results: HPV-16 was the most frequently occurring subtype (53.1%). Patients positive for HPV-16 showed remarkable one-year overall survival (OS) and disease-free survival (DFS) rates of 95.3% and 90.7% respectively compared to those with HPV-18 or other subtypes (p < 0.05). Responders achieving complete treatment response were also the highest in the HPV-16 group while non-HPV-16 cases experienced higher incidences of recurrence and treatment related toxicity. p16 positivity was mostly to HPV-16. Conclusion: HPV subtype plays a critical role in shaping prognosis and treatment outcomes in oropharyngeal cancer. HPV-16 is associated with superior survival and response, suggesting the potential for subtype-specific treatment strategies to improve outcomes